Pengamatan Intensitas Serangan Penyakit Gugur Daun Karet di PT Bridgestone Kalimantan Plantation (BSKP) - Nur Anisah; Salamiah Salamiah; Muhammad Indar Pramudi (www.ulm.ac.id, 2026)
Leaf fall disease is one of the main problems in rubber plant cultivation (Brazilian rubber tree) which can significantly reduce latex productivity. This study aims to observe the intensity of leaf fall disease attacks on rubber plants treated with organic fertilizer plus Trichoderma, Plant Growth Promoting Rhizobacteria (PGPR), and eco-enzymes. Observations were conducted three times in the rubber plantation owned by PT. Bridgestone Kalimantan Plantation (BSKP), using a visual assessment method for disease symptoms and calculating the percentage of infected leaves. The data obtained were analyzed descriptively and quantitatively to determine disease progression trends. The results showed that the application of organic fertilizer plus PGPR was able to suppress disease attacks by 74.50%. followed by other treatments: application of organic fertilizer plus Trichoderma, control plants without application, and organic fertilizer plus Trichoderma supplemented with eco-enzyme, with percentages of attack suppression of 68.97%, 68.83%, and 66.83%, respectively. Air humidity and daily rainfall factors showed a positive correlation with increasing attack intensity. These findings demonstrate the importance of environmentally friendly disease control strategies. This research is expected to form the basis for more effective and sustainable management of leaf fall disease.